2017
DOI: 10.5539/ijef.v9n2p111
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Electronic Banking Services on Bank Transactions

Abstract: The objective of the research was to evaluate the significance of electronic system integrated in the banking sector for providing convenience services to their clients and the overall impact caused by electronic services on bank transaction. The research has applied analytical descriptive methodology to analyze the impact of electronic banking services on the bank transactions. The total sample size taken for the study was 150 and the questionnaires were distributed among the clients and bank officials to col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 2 publications
2
5
0
1
Order By: Relevance
“…However, due to a 1% increase in non-performing loans held by commercial banks will lead to a decline in banking sector development by 0.161 per cent. This positive and significant impact is coherent with the findings by Mishra and Pradhan (2009), Cherif & Dreger (2016), Salamah (2017), andAluko &Michael (2018). This, therefore, means there is a long-run relationship between bank-specific variables and banking sector development.…”
Section: Variablesupporting
confidence: 89%
See 1 more Smart Citation
“…However, due to a 1% increase in non-performing loans held by commercial banks will lead to a decline in banking sector development by 0.161 per cent. This positive and significant impact is coherent with the findings by Mishra and Pradhan (2009), Cherif & Dreger (2016), Salamah (2017), andAluko &Michael (2018). This, therefore, means there is a long-run relationship between bank-specific variables and banking sector development.…”
Section: Variablesupporting
confidence: 89%
“…Banking communication is getting effective and allowing customers to perform as per their will (Parajuli et al, 2020). According to Salamah (2017), electronic banking has a good and significant impact on Nepal's banking sector development. These studies also indicated that customers' security is a big concern for using e-banking services.…”
Section: Review Of Literaturementioning
confidence: 99%
“…In order to make internet banking successful, the aim was to ensure efficacy and value of transactions. With the internet becoming a technology that everybody uses, big banks have created an internet banking system that is ready for companies to use and begin building a customer database (Salamah, 2017). E-banking has many advantages such as lower costs and ease of use via mobile and other electronic devices (Bello, 2010).…”
Section: Electronic Bankingmentioning
confidence: 99%
“…(Mateka, Gogo, & Omagwa, 2016) assessed effects of internet banking on the financial performance of listed Commercial banks in Kenya and the key finding of the study revealed that internet banking has a positive influence on bank incomes, operating costs, and loan book, and customers' deposits. (Salamah, 2016), investigated the Impact of Electronic Banking Services on Bank Transactions and his findings revealed that electronic services have contributed to increasing both the financial activity of the bank as well as the number of its clients. In the banking sector, professional training can be given to banking officials, so that they can effectively work on the electronic system.…”
Section: Empirical Reviewmentioning
confidence: 99%